Non-adiabatic coupling as a frictional force in (He, H, H)+ dynamics and the formation of HeH2+. (16th February 2021) - Ravi, Satyam; Mukherjee, Soumya; Mukherjee, Bijit; Adhikari, Satrajit; Sathyamurthy, Narayanasami; Baer, Michael
Abstract : It is shown that the Born–Oppenheimer–Huang non-adiabatic coupling terms (NACTs) in a molecular Hamiltonian can be considered as equivalent to a friction force in classical mechanics and consequently responsible for the formation of triatomic species like HeH 2 + . The classical equation of motion is solved accordingly for a test case of a helium atom approaching an H 2 + molecule at its potential minimum along the collinear axis and lines parallel to it and also for the C 2 v geometry. It is shown that the singular NACTs between the first two excited states slow down the motion of the three quasi-ions (He, H, H) + while approaching each other and result in substantial loss of kinetic energy in the collision process. These results have profound implications for the formation of di- and triatomic species in the early universe, during the chemical synthesis epoch following the nucleosynthesis that followed the Big Bang. GRAPHICAL ABSTRACT: